DEFINITION REGULATORY CEPHALOMETRIC OPTIONS BY THE METHOD OF TWEED INTERNATIONAL FOUNDATION FOR UKRAINIAN BOYS AND GIRLS - Gunas, І.V.; Dmitriev, М.О.; Prokopenko, S.V.; Shinkaruk-Dykovytska, M.M.; Yeroshenko, G.A. (World of Medicine and Biology, 2017)
In the article the cephalometric parameters which are used in the analysis of Charles H. Tweed International Foundation and their importance for young people Podilskiy region of Ukraine with orthognathic bite, assessment of sexual differences of these parameters and the comparison of obtained results with normative data which are used by Charles H. Tweed International Foundation and normative data of H. Stockfisch for the European population. Established gender and ethnic differences point to the need to create a normative base of cephalometric indicators used in the analysis of Charles H. Tweed International Foundation for the population of Ukraine.
Keywords: lateral teleroentgenogram of the head; cephalometry; Ukrainian boys and girls; Charles H. Tweed International Foundation